GALACTOSEMIA IN NEWBORN CHILDREN - G.V. Yatsyk; T.E. Borovik; M.D. Mitish; T.V. Bushueva; E.P. Bombardirova ("Paediatrician" Publishers LLC, 2007)
Galactosemia is a hereditary disease, the pathogenetic treatment of which is based on dietotherapy. Early diagnosing and the adequate choice of the diet improve the development forecasts for the ill child. The article describes a classical galactosemia case in a newborn. It is shown that despite diagnosing the disease on the second month of life, the adequate selection of etiopathogenetic dietotherapy and etiotropic therapy of the concurrent diseases helped compensate the inborn galactose metabolism defect and optimize the long-term forecast for the child.Key words: inborn metabolism dysfunctions, alactosemia, dietotherapy, newborn children.